Solvent-Free Synthesis of β-Enamino Compounds Promoted by Ferric(III) Ammonium Nitrate - Murthy, Y.L.N.; Venu, R.; Govindh, B.; Diwakar, B.S.; Nagalakshmi, K.; Singh, E.R. (Asian Journal of Chemistry, 2010)
A variety of β-enamino esters and β-enaminones can be synthesized by the reaction of 1,3- dicarbonyl compounds and various primary amines in the presence of catalytic amount of ferric(III) ammonium nitrate at room temperature. This method is simple, requires short reaction times, high yield and the reaction proceeds under solvent-free conditions.